Simulations of geometric aspects for ARAPUCA designs. (1st January 2022) - Adames, M.R.; ,
Abstract: The photon detection system of DUNE Far Detector (FD) is based on ARAPUCA technology. The new version of ARAPUCA, named X-ARAPUCA, will be used in the first and second modules. As the second module is based on vertical drift, the design of the X-ARAPUCA needed to be changed and simulation studies are fundamental for the optimization of the device. This work presents the simulation studies of the design, size, shape, and SiPM positioning inside the reflective cavity. We designed a Python module that creates the geometry for the simulations based on given parameters such as size of the detector, numbers of SiPM and others. The physics of photons inside the X-ARAPUCA is simulated by a ray-tracer written in C++ using an uniform grid as acceleration structure. Our simulations focus on reflections and refractions using Snell's law on the interfaces and the total internal reflections inside the wavelength shifting plate, that absorbs every incoming photon and re-emits them in a random direction. The simulation shows that the highest efficiency is reached for thin X-ARAPUCA with a square shape. Better efficiency is obtained for larger modules if one considers the number of SiPM per cm 2 of the active collection area. Rectangular modules are more efficient when the SiPMs are positioned on the short side.